2020
DOI: 10.1155/2020/3692937
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Otic Lineages from Integration-Free Human-Induced Pluripotent Stem Cells Reprogrammed by mRNAs

Abstract: Damage to the sensory hair cells and the spiral ganglion neurons of the cochlea leads to deafness. Induced pluripotent stem cells (iPSCs) are a promising tool to regenerate the cells in the inner ear that have been affected by pathology or have been lost. To facilitate the clinical application of iPSCs, the reprogramming process should minimize the risk of introducing undesired genetic alterations while conferring the cells the capacity to differentiate into the desired cell type. Currently, reprogramming indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Furthermore, these lines then successfully further differentiated into hair cell and neuronal lineages. The findings of this study indicate that mRNA-reprogrammed iPSCs are just as capable of producing otic lineages as lentivirus-induced ones while also being safer for clinical applications [27]. Overall, iPSCs in each study demonstrated that they are viable options for regenerating cells in the inner ear; however, more work still needs to be done to improve the survival and differentiation of iPSCs in the cochlea [24].…”
Section: Induced Pluripotent Stem Cell (Ipsc) Therapymentioning
confidence: 74%
“…Furthermore, these lines then successfully further differentiated into hair cell and neuronal lineages. The findings of this study indicate that mRNA-reprogrammed iPSCs are just as capable of producing otic lineages as lentivirus-induced ones while also being safer for clinical applications [27]. Overall, iPSCs in each study demonstrated that they are viable options for regenerating cells in the inner ear; however, more work still needs to be done to improve the survival and differentiation of iPSCs in the cochlea [24].…”
Section: Induced Pluripotent Stem Cell (Ipsc) Therapymentioning
confidence: 74%
“…Therefore, FoxG1 might affect the occurrence and development of age-related hearing loss by regulating multiple pathways. Foxg1 as one of the marker genes of inner ear progenitor cells and plays an important role in the process of inducing pluripotent stem cells to differentiate into inner ear cells ( Boddy et al, 2020 ). Therefore, the Foxg1 -related reprogramming technology has great application value to regenerate cells in the inner ear that are affected by pathology or damage.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these protocols carried out completely in two‐dimensional (2D)‐cultures using treatments with a combination of small molecules and/or recombinant proteins to manipulate key signaling pathways of the inner ear development. The differentiation under 2D‐cultures can provide a relatively homogenous population of otic sensory progenitors and initial HC‐like cells in prolonged cell cultures 23‐26 . In contrast to 2D‐culture system, the induction of PSCs under three‐dimensional (3D)‐organoid strategy allows for the generation of multiple cell types and recapitulates, to some extent, in vivo composition of an inner ear sensory epithelium containing HC, supporting cell and sensory neuron‐like cells 27‐29 .…”
Section: Inner Ear Neurosensory Cell Induction Strategies From Hipscsmentioning
confidence: 99%